Investigation of morphological and optical properties of nanostructured layers formed by the SSCT etching of silicon - Jurečka, Stanislav; Imamura, Kentaro; Matsumoto, Taketoshi; Kobayashi, Hikaru (Applied Surface Science, 2018)
[Display omitted] •Forming of the nanostructured SSCT layers.•Analysis of microstructure by statistical, Abbott-Firestone, Fourier and multifractal methods.•Analysis of density of vibrational states by Raman scattering. Nanostructured layers were formed on silicon substrate by using metal assisted etching method with different etching times. Microstructural properties of prepared layers were experimentally studied by the electron microscopy methods and analysed by the statistical methods, by the Abbott-Firestone method, by analysis of the power spectral density and by using methods of fractal geometry. Results of microstructure analysis show forming of particle size distribution in the volume of etched layer and its development during the structure preparation. Raman scattering was used for the determination of density of vibrational states related to formed particle size distribution.